2015
DOI: 10.1007/s10493-015-9960-x
|View full text |Cite
|
Sign up to set email alerts
|

Deltamethrin resistance in field populations of Rhipicephalus (Boophilus) microplus (Acari: Ixodidae) in Jammu and Kashmir, India

Abstract: Detection of resistance levels against deltamethrin in Rhipicephalus (Boophilus) microplus collected from six districts of Jammu and Kashmir (India) was carried out using the adult immersion test. The regression graphs of probit mortality of ticks plotted against log values of concentration of drug were utilised for the determination of slope of mortality, lethal concentration for 50% (LC50), 95% (LC95) and resistance factor (RF). On the basis of the data generated on mortality, egg mass weight, reproductive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Also, Eshetuet al, (2013) who studied the in vitro efficacy of diazinon 0.06% against Rhipicephalus pulchellus and Amblyomma gemma using modified adult immersion test and found that after 7 days incubation of females, Diazinon 0.06% cause control of oviposition by 88.85% and 71.41% in A. gemma and R. pulchellus, respectively. The results of the current study also confirmed by Ahanger et al, (2015) who observed that the increase in concentration of the deltamethrin could not cause mortality in all the exposed ticks but the egg laying capacity or the efficacy of conversion of live weight into egg mass decreased among the surviving ticks. On the other hand, these results were disagreed with results obtained by Kumar et al, (2016) who tested Butox ® 0.003 % Vet (containing 1.25% deltamethrin) against field ticks and resistant tick lines and found that the product led to 1.5-7.7 % inhibition of oviposition in resistant tick lines.…”
Section: Discussionsupporting
confidence: 88%
“…Also, Eshetuet al, (2013) who studied the in vitro efficacy of diazinon 0.06% against Rhipicephalus pulchellus and Amblyomma gemma using modified adult immersion test and found that after 7 days incubation of females, Diazinon 0.06% cause control of oviposition by 88.85% and 71.41% in A. gemma and R. pulchellus, respectively. The results of the current study also confirmed by Ahanger et al, (2015) who observed that the increase in concentration of the deltamethrin could not cause mortality in all the exposed ticks but the egg laying capacity or the efficacy of conversion of live weight into egg mass decreased among the surviving ticks. On the other hand, these results were disagreed with results obtained by Kumar et al, (2016) who tested Butox ® 0.003 % Vet (containing 1.25% deltamethrin) against field ticks and resistant tick lines and found that the product led to 1.5-7.7 % inhibition of oviposition in resistant tick lines.…”
Section: Discussionsupporting
confidence: 88%
“…Among these pesticides, the synthetic pyrethroids, deltamethrin and flumethrin, are commercially available in India and presently the predominant acaricides used to control tick in the country [ 4 , 5 ]. There are reports indicating development of various grade of resistance against pyrethroids in field strains [ 3 , 5 7 ]. Besides this, fipronil is a part of new generation of products used to combat invertebrates [ 8 ] and has been recently introduced in the Indian market.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first report of synthetic pyrethroid resistance in R. microplus in Australia in 1989, there have been continuous reports of resistance to this class of acaricides globally [ 28 30 ]. Studies from different countries have shown that different mutations in the VGSC gene of R. microplus lead to different resistance phenotypes.…”
Section: Discussionmentioning
confidence: 99%